Delivery management of industrial product-service systems – challenges for a performance measurement - Meier, Horst; Dorka, Thomas; Morlock, Friedrich (Cranfield University Press, 2013)
In the manufacturing industry, competitors are continuously struggling to differentiate themselves from other companies in the market. Industrial product-service systems (IPS²) offer this differentiation by representing a paradigm shift from traditional product selling and service offering to providing customer value. During the use phase of IPS², the organisation and planning are executed and managed by the IPS² execution system (IPS²-ES). To ensure and improve the effectiveness and efficiency of the IPS²-ES during the use phase, a performance measurement is needed. This paper presents a motivation for a performance measurement during the delivery phase and based on this the requirements for the performance measurement are introduced. An outlook for further research will be given.
Keywords: Performance measurement; industrial product-service system (IPS²); planning